Into the dark : seeing the sacred in the top films of the 21st century - Detweiler, Craig, 1964- (Grand Rapids, Mich. : Baker Academic, 2008)
In Into the Dark, Craig Detweiler, a well-respected film expert and media spokesperson on Hollywood and Christianity, examines forty-five twenty-first-century films that resonate theologically--from The Lord of the Rings trilogy to Little Miss Sunshine--offering groundbreaking insight into their scriptural connections and theological applications. Detweiler uses the IMDb, the wildly popular Internet Movie Database, to select today's most influential contemporary films. Into the Dark dissects the theology of everyday life, exploring the work of the Spirit of God in creation and redemption to discuss "general revelation" through cinema and sometimes unlikely filmmakers. "Memory, community, and imagination offer a strong starting place for theological reflection," Detweiler writes. Driven by the art of the films, Into the Dark opens up lively discussion topics, including anthropology, the problem of evil, sin, interconnectivity, postmodern relationships, ethics, fantasy, and communities in crisis. Notable movies discussed include Gladiator, United 93, Million Dollar Baby, and Walk the Line. This book is recommended for college and seminary students in film, theology, and communications courses as well as pastors, film fans, and those interested in Christianity and the cinema. - Publisher.
Preface: A Hornet's nest -- Methodology: Into the Darko -- pt. 1. Identity. Memento : duped in film noir -- Eternal sunshine : the risky rewards of romance -- pt. 2. Community. Crashing into the ensemble drama : communities in crisis -- Talk to her (and him and us) : everyday ethics -- pt. 3. History. Finding Neverland : nostalgia and imagination in history -- Spirited away by fantasy : tending the garden -- Conclusion: Mnemonic devices -- Appendix A: Top 250 movies as voted by IMDb users (January 1, 2007) -- Appendix B: The IMDb's top films of the 21st century (January 1, 2007) -- Appendix C: The IMDb's top films of the 21st century (April 15, 2008).
Includes bibliographical references (pages 293-312) and indexes.
Includes filmographies.
Keywords: Motion pictures -- Religious aspects; Motion pictures -- Moral and ethical aspects